Cognitive to physical performance: a conceptual model for the role of motor simulation in performance - McNeill, E.; Toth, A. J.; Harrison, A. J.; Campbell, M. J. (International Review of Sport and Exercise Psychology, 2020)
Motor simulation (MS) interventions incorporating motor imagery (MI), and more recently action observation (AO), are readily accepted as effective interventions to enhance motor skill performance. Existing models in the MS literature fail to consider the entire spectrum of MS interventions, focusing on MI or AO alone. This paper examines the theoretical basis and current understanding of MS efficacy, and introduces a novel, conceptual, Motor Simulation and Performance Model (MSPM) representing the performance improvements predicted to be associated with engaging with MS across expertise levels. The MSPM also outlines the multiple factors which regulate the efficacy of MS interventions. Based on the available evidence, the model suggests that MI will have a greater relative effect on performance as expertise increases, AO will have a greater effect in low skilled compared to high skilled performers, and that combined AO and MI (AO + MI) will be more effective than either MI or AO in isolation. The MSPM also depicts the additive effect of physical practice in conjunction with MS interventions. The MSPM represents for the first time the relative effects of various methods of motor learning based on evidence provided by the existing literature. It also highlights areas of research requiring further attention.